#
- If a,b,c are in A.P and X,Y,Z are in G.P then prove( X
^{b-c})x (Y^{c-a}) x(Z^{a-b})=1 - In a G.P t
_{p+q}=m and t_{p-q}=n. Then find t_{p}.

^{b-c})x (Y^{c-a}) x(Z^{a-b})=1_{p+q}=m and t_{p-q}=n. Then find t_{p}.The question should be;

**If a,b,c are in A.P and X,Y,Z are in G.P then prove( X**

^{b-c})x (Y^{c-a}) x(Z^{a-b})=1given: a , b and c are in AP. therefore

or

X , Y and Z are in GP, therefore

LHS of the given equation:

which is the required result.

hope this helps you.

cheers!!

**
**